Effect of shearing prestrain on the hydrogen embrittlement of 1180 MPa grade martensitic advanced high-strength steel. (1st May 2022) - Li, Huixing; Venezuela, Jeffrey; Zhou, Qingjun; Shi, Zhiming; Yan, Ming; Knibbe, Ruth; Zhang, Mingxing; Dong, Futao; Atrens, Andrej
Abstract: This work investigated the effect of shearing prestrain on hydrogen embrittlement. The strength and ductility values were similar to those in air for hydrogen precharging before tensile testing, but the ductility decreased significantly for tensile testing with in-situ hydrogen charging due to intergranular fracture initiation at the specimen surface. In contrast, there was a significant decrease in ductility for the hydrogen precharged steel after prestrain. The hydrogen-facilitated fracture was transgranular. The hydrogen fracture grew by fracture tip blunting, new fracture initiation, and coalescence, consistent with a hydrogen enhanced localized plasticity (HELP) mechanism. Highlights: Internal hydrogen had minimal influence on the mechanical properties of MS 1180 with no prestrain. Internal hydrogen plus prestrain decreased tensile strength by 4% and elongation by 42%. The hydrogen fracture mode was intergrannular in unstrained MS 1180. Hydrogen fracture was transgrannular in prestrained MS1180, due to trapped hydrogen and the increased dislocation density. The hydrogen-facilitated fracture mechanism was hydrogen enhanced localized plasticity.